От Архаической Скифии к Классической - Гречко, Д.С. (Археологія і давня історія України, 2016)
В статье рассматриваются вопросы микрохронологии материальной культуры VI в. до н. э. и детализруется история кочевого и оседлого населения юга Восточной Европы в это время. Анализируются
погребальный обряд и материальная культура переходного периода. У статті робиться спроба деталізувати розвиток
матеріальної культури та етнокультурної історії населення півдня Східної Європи у VI ст. до н. е. Є підстави вважати, що Давня Скіфія з її ранньоскіфської матеріальним комплексом поступово поступилася місцем Класичній в середині-другій половині VI ст.
до н. е. під впливом нової групи кочовиків, яка прийшла з Північного Кавказу через пониззя Дону
до Північного Причорномор’я. There is an attempt to make more detailed the development
of material culture and ethnical-cultural
history of the population of the South of the Eastern
Europe in the 6th century BC in this article. We consider
that the Early-Scythian material complex of Ancient
Scythia had transformed to the Classical model gradually
in the middle—second half of the 6th century BC.
This happened under the influence of new groups of nomadic
tribes which penetrated from the Northern Caucasia
through the Lower Don to the Northern Black Sea
area. These groups were not homogeneous and could
include nomads of the Pre-Caucasus and Pre-Kuban
areas of early-Scythian time in their structure and the
new groups of nomadic tribes from the more Eastern
areas (Pre-Ural, Tuva, Eastern Turkestan). We couldn’t exclude the participation of the part of Scythians — the
last who had returned from the West Asia. The gap in the existence of the monuments of two these periods is
not marked. The migration of the middle of the 6th century BC was the next displacement of the tribes of the
Northern Caucasia to the Northern Black Sea area. These groups of the new population didn’t subordinate
the population of Forest-Steppe area — admittedly because they were not numerous. Exactly they have
brought the part of new cultural and material complex (new type of a horse bridle, armament, forms of animal
stile etc.) to the region. However the traditions of more numerous migrants of the last quarter of the VI c.
BC from the Northern Caucasus had more influence to the forming of the material culture of Classical Scythia.
This marked by the appearance of a significant number of individual burial places and burial grounds.